Information Sharing and Dissemination by Use of Mailing Lists - Pujar, Shamprasad M.; Manjunath, G.K.; Juttiyavar, Mahesh N. (DESIDOC Journal of Library & Information Technology, 2003)
Mailing lists are vital communication tools used by the academic and research community for sharing knowledge and to discuss latest developments and related issues in specific subject area. These also serve as forum for seeking technical assistance or sharing such knowledge in an informal way by cutting all the geographical barriers. This article intends to highlight the usefulness of mailing lists, with a special reference to librarians, highlights the issues related to the mailing lists and also annotates the popular mailing lists in the field of library and information science. http://dx.doi.org/10.14429/dbit.23.6.3611